Hasil Pemeriksaan TB Paru Metode TCM pada Tersangka TB Paru - Muhajir Muhajir (Poltekkes Kemenkes Semarang, 2021)
Tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (MTB). Determinants of pulmonary TB disease include gender, and age. The Rapid Molecular Test Method (TCM) is a breakthrough TB program for Drug Resistant TB patients. The TCM method takes two hours to get the patient's diagnosis. TCM method for diagnosing TB and resistance to rifampin quickly and accurately. Tidar Magelang Hospital is one of the referral places for TCM examinations from various health facilities. The purpose of this study was to describe the results of the TCM method of pulmonary TB examination on pulmonary TB suspects at Tidar Magelang Hospital. This type of research is descriptive. The research data is secondary data obtained from Tidar Hospital Magelang. Based on age, namely early adolescence, late adolescence, early adulthood, late adulthood, early elderly, late elderly, and seniors, the results were sensitive rif 0.76%, 11.45%, 9, 54%, 7.25%, 5.73%, 8.78% and 3.82%. Negative results 1.15%, 1.91%, 6.87%, 7.25%, 7.63%, 14.89% and 12.98%. The rif results were sensitive to 27.1% males and 20.23% females. Negative results in 31.3% men and 21.37% women. The most sensitive rif results are in Magelang, followed by Magelang City, then East Jakarta Municipality, Banjarnegara and Purworejo. Negative results were found in Magelang, followed by Magelang City, then Wonosobo and East Waringin City.